Compensation and Employee Competency Development in Improving Employee Performance at PT. Bahtera Sarana Cargo - Parluhutan Siahaan, Christian Devid; Cici Handayani; Dewi Wulandari (Jurnal Ekonomi, 2025)
This study aims to analyze the effect of compensation and competency development on improving employee performance at PT. Bahtera Sarana Cargo. The results of the study indicate that compensation based on job level, attendance level, and employee permanence status contributes positively to employee motivation and loyalty. In addition, incentives and bonuses have been shown to encourage employees to demonstrate optimal work performance. On the other hand, employee competency development through training and skill development has also been shown to improve employee work ability and readiness in facing the company's operational challenges. Both factors synergistically support the creation of better and sustainable employee performance. This study emphasizes the importance of strategic human resource management in improving company competitiveness through superior employee performance.